Perspective of coaches on LTAD of elite judo athletes: A comparative analysis - Nolte, P. L.; Burnett, C.; Hollander, W. (South African Journal for Research in Sport, Physical Education and Recreation, 2017)
Plans for Long-Term Athlete Development (LTAD) can only have effect by way of optimal management of resources. The Sports Policy Factors Leading to International Sporting Success (SPLISS) provides a theoretical model for policy factors that account for the functioning of elite sport systems and ultimately the performance of elite athletes. Underpinned by resource dependence theory, this study reports on the impact of the management of elite sport systems on the career development of elite judo athletes in three countries. A mixed-methods comparative case study between elite judo coaches, defined by their status as national coaches, from South Africa (n=14) and two internationally successful judo countries, the Netherlands (n=6) and England (n=6), was conducted. Data was gathered by means of questionnaires (n=26) and semi-structured interviews (n=6). The results indicate that the optimal management of multiple resources anticipates successful performance pathways in elite sport systems.